(untitled) (Communications in Computational Chemistry, 2018)
Clone the Harvoni^TM(Sofosbuvir/Ledipasvir) tablet manufactured by Gilead Sciences, Inc. and screen out the best formula of prescription, to make the pesticide effect of prepared tablet was equal to the original tablet. Methods: Based on the prescription of HarvoniTM manufactured by Gilead Sciences, Inc., the compatibility test of the excipient with the active ingredient was carried out. The stability of self-made samples and reference preparations were investigated, which includes high temperature, high humidity and light conditions. According to the above test, the most reasonable prescription process was chosen. Results: The determined prescription process contained sofosbuvir (400mg), ledipasvir (90mg), copovidone (97.5mg), croscarmellose sodium (50mg), microcrystalline cellulose (115mg), lactose monohydrate (230mg), magnesium stearate (7.5mg), gum arabic(10mg), opadry film coating powder, and purified water. Conclusion: The determined prescription process was stable and the pesticide effect of prepared tablet was equal to the original tablet, so the prescription design was reasonable.